Lineabilidade do conjunto dos operadores lineares limitados não absolutamente somantes - Ferreira, Marcos dos Santos (2010)
In this work we present some results involving lineability and the linear theory of absolutely summing operators. We note that the technique presented is closely related to the theory of hereditarily indecomposable Banach spaces and that the presence of an unconditional basis in one of the spaces involved is crucial to guarantee some results.